2019
DOI: 10.3103/s1067821219030143
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation into the Influence of Overheating of Aluminum Melt on the Heat Exchange in the Continuous Combined Casting and Pressing

Abstract: The results of a numerical investigation into the temperature-temporal dependences in continuous combined casting and pressing of the AK12 experimental aluminum alloy at a different overheating temperature from startup to the instant the steady-state thermal conditions are reached by the installation are reported. Calculations are performed based on a three-dimensional computer model of a complex heat exchange in an installation of a new design equipped by a horizontal rotary crystallizer. Theoretical investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The supply of liquid metal into the groove, its solidification and extrusion proceed in a continuous mode [27]. 1die stopper; 2press product; 3stationary arcuate segment; 4solidified ingot; 5metal melt; 6dispenser; 7crystallizer wheel; 8annular groove A necessary condition for combining continuous casting and extrusion of metal is the observance of such thermal conditions in the "metal-crystallizer-environment" system, which ensures the solidification of the melt and stabilization of its temperature in the section in front of the container [28][29][30]. An analysis of the thermal regimes of continuous casting before extrusion of aluminum alloys carried out on the basis of the method proposed in [31,32] that confirmed this statement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The supply of liquid metal into the groove, its solidification and extrusion proceed in a continuous mode [27]. 1die stopper; 2press product; 3stationary arcuate segment; 4solidified ingot; 5metal melt; 6dispenser; 7crystallizer wheel; 8annular groove A necessary condition for combining continuous casting and extrusion of metal is the observance of such thermal conditions in the "metal-crystallizer-environment" system, which ensures the solidification of the melt and stabilization of its temperature in the section in front of the container [28][29][30]. An analysis of the thermal regimes of continuous casting before extrusion of aluminum alloys carried out on the basis of the method proposed in [31,32] that confirmed this statement.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time on the basis of computer simulation it was found that the degree and rate of heating of the crystallizer in the initial period of operation of the installation have the main effect on the nature of unsteady heat transfer and changes in the enthalpy of the melt [33,34]. As a result, operational and design solutions were proposed that ensure rational temperature-time conditions for the installation at a fixed design rotational speed of the mold (the productivity of the installation in terms of the mass flow rate of the melt poured in) in a long-term stable period of its operation [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The supply of liquid metal into the groove, its solidification and extrusion proceed in a continuous mode [27]. A necessary condition for combining continuous casting and extrusion of metal is the observance of such thermal conditions in the "metal-crystallizer-environment" system, which ensures the solidification of the melt and stabilization of its temperature in the section in front of the container [28][29][30]. An analysis of the thermal regimes of continuous casting before extrusion of aluminum alloys carried out on the basis of the method proposed in [31,32] that confirmed this statement.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time on the basis of computer simulation it was found that the degree and rate of heating of the crystallizer in the initial period of operation of the installation have the main effect on the nature of unsteady heat transfer and changes in the enthalpy of the melt [33,34]. As a result, operational and design solutions were proposed that ensure rational temperature-time conditions for the installation at a fixed design rotational speed of the mold (the productivity of the installation in terms of the mass flow rate of the melt poured in) in a long-term stable period of its operation [29,30].…”
Section: Introductionmentioning
confidence: 99%